A two dimension numerical model for waves induced currents in the coastal zone - Hoan, Le Xuan; Hung, Nguyen Manh (Vietnam Journal of Mechanics, 2003)
In this paper, the results of two dimension numerical model for waves induced currents in the coastal zone are presented. The model was adjusted and verified at Phan Ri-Binh Thuan zone. The results of the testing show a good agreement between the observed and computed values. Then the model is applied to calculation of the distribution of waves induced currents in Ly Hoa area.